The some aspects of international combating terrorism at various stages of international law - Трофімцов, Владислав Анатолійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In the article in order to establish the legal basis for the development of counter-terrorism in the world analyzed the main international legal instruments. Focus on the importance of international organizations such as the Council of Europe and the United Nations to identify and provide the right qualifications unlawful act of the offender (group of persons), means of prevention, prevention, control and combating terrorist acts. It is concluded that a direct connection to the legal principles and the historical stages of development of terrorism in the world. Relevance of the topic is that the processes of formation and development of the rule of law are impossible without the formation and development of effective administrative and criminal legal leverage over socially dangerous phenomenon, which entail legal consequences of the offensive. It may be administrative offenses, criminal offenses or offenses that go beyond the rules of conduct ratified by the individual (groups of persons, groups, legal persons or other entities) in the society by the competent public authorities, their officials and officers, as the will of the society in the interests of territorial political entity on the international scene. In addition, the recent widespread cases of promotion of dynamic-resistant and socio-long organized crime, attracting considerable effort and resources to achieve a common criminal intent to violate the status of the state system in the country, undermining the national security of the state in the foreign card, assault sustainable functioning of the organs of state power or local government, health and life of ordinary citizens, members of international organizations, employees of eligible entities and the like, in general, is characterized by a system of organized terrorism. Despite the considerable amount of work in the study area, some aspects of counter-terrorism went unheeded scientists, one of these problems is the study of problem issues of formation and development of legislation in the field of counter-terrorism. Said fully underlines the relevance of the theme of this study and formulate the purpose of this article, which is visible in the establishment of the historical and legal basis of the development of terrorism in the world. The findings concluded that given the large number of international legal acts in the sphere of combating terrorism, the following areas of counter-terrorism at various stages of development of international law: international legal regulation to counter terrorist acts of unlawful seizure of aircraft; international legal regulation to counter terrorist acts of unlawful seizure of water transport; International legal regulation of countering terrorist acts related to illegal content individuals (officials or officials of eligible public authorities, business entities, non-governmental organizations); International legal regulation of countering terrorist acts related to illegal abduction of persons enjoying special right of international protection (the heads of other states, heads of security agencies, diplomatic agents, consuls and their family members) international legal regulation to counter terrorist acts of unlawful seizure of administrative buildings ; international legal regulation to counter terrorist acts of unlawful seizure of land transport; International legal regulation of countering terrorist acts related to illegal use of (using) automatic firearms, explosives, chemical weapons (of mass destruction), or funds for jet propulsion.